Epidermal growth factor receptor immunohistochemistry in different histological types of infiltrating breast carcinoma. Issue 11 (November 1993) - Martinazzi, M; Crivelli, F; Zampatti, C; Martinazzi, S
Abstract : AIMS–To determine the immunohistochemical expression of epidermal growth factor receptor (EGF-R) in high grade, intermediate, and low grade tumours. METHODS–Specimens from 931 breast carcinomas were partly formalin fixed and paraffin wax embedded, to classify cases, and partly frozen in liquid nitrogen, cryostat sectioned, and immunostained using two monoclonal antibodies from clone 455 and 528 to demonstrate EGF-R positive cells. An avidin-biotin complex and peroxidase method was used after incubation with biotinylated anti-mouse antibody; colour was developed using a diaiminobenzidine solution. RESULTS–Low grade carcinomas seldom expressed EGF-R (n = 3) compared with 106 high grade infiltrating ductal carcinomas: EGF-R positive cases were much less common in infiltrating lobular than in infiltrating ductal carcinoma. Medullary carcinomas did not differ from infiltrating ductal carcinomas. CONCLUSIONS–The very low incidence of EGF-R positive cases in the "special type" group of breast carcinomas with a good prognosis is in line with the absence of the homologous c-erbB-2 and p53 oncoproteins, and the rarity of highly proliferating and oestrogen/progesterone negative cases. EGF-R expression in infiltrating lobular carcinoma was in keeping with the intermediate behaviour of this kind of tumour. EGF-R expression in cases of pure medullary carcinoma is the same as that of high grade tumours.